Reconciling work and family life in EU law and policy - Caracciolo di Torella, Eugenia; Masselot, Annick (Basingstoke, 2010)
"The tension that exists in trying to combine family and work responsibilities has long been acknowledged at the European Commission level. There are clear economic implications, for example, if reconciling work and family life is successful (or not). Societal attitudes have also changed: mothers now take for granted their productive as well as reproductive roles and fathers are increasingly willing to take part in their children's lives. The role of parenting has changed but has the law changed to meet individuals' new expectations? There are also challenges involved in trying to reconcile work and family life when caring for the elderly and sick members of the family. Since its timid introduction onto the EC agenda in 1974, reconciliation has developed into a fully articulated principle. This book explores this journey and its implications for the EC legal order and society. It offers a new conceptual approach based on an innovative classification of the existing EU measures (leave, time and care)."